A comunicação suplementar e/ou alternativa no contexto educacional - Lima, José Luiz de (2013)
Introduction: considering that language and social interactions are substantial parts of our character, the goal of this study is to present elements that allow an analysis of the aspects related to the improvement of oral language in persons with severe impairments in oral communication. Objective: This study has the purpose of analyzing aspects related to the use or not of CSA by teachers working in special education with students who present serious limitations with regard to oral language, such as: the concept of CSA as formulated by the teachers; the use of CSA by the teachers; the teachers' initial and continued education on CSA. Method: Fifty teachers from three different special schools within Curitiba's Metropolitan Area took part of the study. The survey comprised questionnaires wish open and closed questions. Results: From the total sample, only 36% reported that they use CSA, although 88% of them showed some interest in using it should there be any support for that. A significant 52% did not consider CSA as a relevant resource for improving the teaching and learning processes; and another 24% did not have any preconception of CSA. Only 2% referred that CSA was part of their undergraduate curriculum and 26% took additional courses on CSA after graduation. It became clear that such courses provided only superficial information on CSA, with a small teaching load, thus not providing in-depth knowledge on the subject matter. Conclusion: it is concluded that there is a general predisposition and willingness from the teachers towards the use of CSA. But the study shows that there are large gaps in formal knowledge on CSA at undergraduate level of those who use CSA.